Trade, global value chains, and small and medium-sized enterprises in Thailand: A firm-level panel analysis - Upalat Korwatanasakul; Sasiwimon Warunsiri Paweenawat (Asian Development Bank Institute (ADBI), 2020)
This study assesses the determinants of global value chain (GVC) participation and the relationship between the degree of GVC participation and firms' performance. The main estimation method for both analyses is a panel fixed-effect regression employing unique panel firm-level data from the Office of Industrial Economics, Ministry of Industry, Thailand for the period 2004-2014. Our results show that small and medium-sized enterprises (SMEs) have a lower degree of engagement in both backward and forward GVC participation when compared with larger firms (non-SMEs). This study also finds that GVC participation, both backward and forward participation, is positively associated with firms' performance. Our results imply that being an SME is associated with a lower degree of GVC participation, but GVC participation can help firms (both SMEs and large firms) increase their revenues. Hence, policies to help local SMEs to enter GVCs smoothly would be the priority.
Keywords: F13; F14; L11; L25; L26; O24; 330; global value chain; GVC; small and medium-sized enterprises; SMEs; Thailand; firm level; panel analysis